DETERMINATION OF HEAVY METALS ARSENIC AND CADMIUM IN THE REFILL DRINKING WATER IN PURWOKERTO - Sri Royani; Adita Silvia Fitriana (LLDIKTI Wilayah X, 2020)
Refill drinking water production is now rapidly increasing in several regions in Indonesia, including Purwokerto. According to the Regulation of Health Minister of the Republic of Indonesia (Permenkes) Number 492/Menkes/Per/IV/2010, heavy metal is one of the parameters of drinking water quality which has adverse impacts on human health. In this study, Arsenic (As) and Cadmium (Cd) would be studied. Atomic Absorption Spectrometry (AAS) Method was used to find As and Cd concentration in refill drinking water samples. The results showed that only one sample containing As from five samples was collected, but there is being safe for drinking according to Regulation of Health Minister of the Republic of Indonesia (Permenkes) Number 492/Menkes/Per/IV/2010. Meanwhile, Cd was not detected in samples. It can be concluded that refill drinking water samples that were taken from several depots in Purwokerto City are being safe for drinking.